Comprensión lectora y resolución de problemas matemático en estudiantes del sexto grado de primaria de la institución educativa primario secundario Nº 60189 de la localidad de Santa María del distrito de Alto Nanay – 2017 - Gonzales Núñez, Hugo (2017)
The elaboration of the present Thesis is done taking into account the new opinion and regulation that came out on the so-called plagiarism of documents in the different Universities of Peru and the world; there are appreciations, theories, applications that we take from certain experience about the problems to study. There are many theories regarding the problem taken in this thesis, since this problem of reading comprehension and mathematical problem solving in the sixth grade of primary education. We can notice in the student of the rural area with more clarity, knowing that for the reading comprehension of a boy or girl of the first grade of the primary level they do not have the capacity of the reading writing until approximately the fourth grade of primary school; that is why as parents of families and teachers we must give great importance to the apprehension of our children and students, from the initial education level. We can also indicate that the parents of the rural area have a higher percentage who have not finished their primary education and a much lower percentage do not have secondary education. The present study is carried out in the I.E. P.S.M. Nº 60189 of the district capital of Alto Nanay, of the province of Maynas, Loreto region, alma mater where we arrived to work many years as a teacher of said educational institution. We can also outline the problem of low compression in students by geography of the district's jurisdiction with communities distant from the district capital and much more from the city of Iquitos, such as: for the basin of the Pintuyacu river and Chambira river , the only transport is water and this transport is not permanent, another collateral problem is the effective permanence of teachers throughout the year and there are educational institutions that do not have teachers for many years; All these problems affect our children from our riverside of Nanay and this is related to the ability to understand reading. Reading comprehension is not only to recognize letters and words, but to understand the message that the author wants to communicate, that is, literal understanding; until arriving at the inference comprehension